THE INFLUENCE OF CONFLICT MANAGEMENT AND WORK ENVIRONMENT ON THE EMPLOYEES PERFORMANCE OF PT Bank Tabungan Negara Tbk - Dewi Puspaningtyas Faeni; Fiqria Nur Ramadhan (IJESM Indonesian Journal of Economics and Strategic Management, 2024)
This research is a literature study that examines the relationship between conflict management and work environment on performance. This research focuses on examining employee performance at PT Bank Tabungan Negara Tbk. This research uses a quantitative method approach with a population of PT Bank Tabungan Negara Tbk employees.